2004
DOI: 10.1007/s00251-004-0741-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and expression analysis of interleukin 2 (IL-2) and IL-21 homologues in the Japanese pufferfish, Fugu rubripes, following their discovery by synteny

Abstract: This investigation provides the first conclusive evidence for the existence of the interleukin 2 (IL-2) and IL-21 genes in bony fish. The IL-2 and IL-21 sequences have been determined in Fugu rubripes by exploiting the conservation of synteny that is found between regions of the human and Fugu genomes. The predicted 149-amino acid IL-2 homologue contains the IL-2 family signature, has a predicted secondary structure of three alpha helixes and has the two cysteines important in disulphide-bond formation. It sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 98 publications
5
81
0
Order By: Relevance
“…1). This gene organization is consistent with the tetraodon IL-21 organization (32), but different to that reported for fugu IL-21, where a five-exon/four-intron structure was found as seen in mammals (31). To gain further insight into the fish IL-21 gene organization, we analyzed another fish IL-21 gene from zebrafish where the genomic (accession number NW_001880637) and cDNA (accession number EF143579) sequences of this gene are available in the database.…”
Section: Identification and Sequence Analysis Of The Il-21 Gene In Rasupporting
confidence: 65%
See 4 more Smart Citations
“…1). This gene organization is consistent with the tetraodon IL-21 organization (32), but different to that reported for fugu IL-21, where a five-exon/four-intron structure was found as seen in mammals (31). To gain further insight into the fish IL-21 gene organization, we analyzed another fish IL-21 gene from zebrafish where the genomic (accession number NW_001880637) and cDNA (accession number EF143579) sequences of this gene are available in the database.…”
Section: Identification and Sequence Analysis Of The Il-21 Gene In Rasupporting
confidence: 65%
“…The final two exons of IL-21 are equivalent to the final exon of its relatives IL-2 and IL-15. Analysis of the trout gene and other fish genes revealed that the fish IL-21 genes have a common six-exon/five-intron gene organization, with the exception of fugu IL-21 that has only five exons (31). Examination of the sizes of the exons suggests that exons 3 and 4 in fish IL-21 are equivalent to exon 3 in mammals (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations